The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2139/ssrn.3412326
|View full text |Cite
|
Sign up to set email alerts
|

The New Intergovernmentalism and the Euro Crisis: A Painful Case?

Abstract: The new intergovernmentalism seeks to understand the changing dynamics of contemporary European integration. It emphasises, inter alia, member states' preference for deliberative modes of decision-making and their reluctance to delegate new powers to traditional supranational institutions. The euro crisis is sometimes seen as a difficult case for the new intergovernmentalism because of the perceived importance of hard bargaining over crisis measures during this episode and the new roles entrusted to the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Second, this article not only lends support to the new intergovernmentalist claims, but also expands theory's empirical scope to crisis situations. The new intergovernmentalism has been launched 'to understand the changing dynamics of European integration in the post-Maastricht period', and was criticized for failing to address the institutional dynamics set in motion by crisis situations (Hodson 2020). The analysis demonstrated that the EU's handling of the European refugee crisis is largely consistent with the key claims of new intergovernmentalism.…”
Section: Conclusion: Failed Intra-european Solidarity the Airmation mentioning
confidence: 99%
“…Second, this article not only lends support to the new intergovernmentalist claims, but also expands theory's empirical scope to crisis situations. The new intergovernmentalism has been launched 'to understand the changing dynamics of European integration in the post-Maastricht period', and was criticized for failing to address the institutional dynamics set in motion by crisis situations (Hodson 2020). The analysis demonstrated that the EU's handling of the European refugee crisis is largely consistent with the key claims of new intergovernmentalism.…”
Section: Conclusion: Failed Intra-european Solidarity the Airmation mentioning
confidence: 99%
“…The consensus‐seeking practices arising from this – whether in the preparation, decision‐making or communique, much like the Council/COM – has been integral to the considerable success story that is the NSMC (a body that is now the custodian of some 156 areas of cross‐border co‐operation) (McCall, 2021, p. 27). The NSMC – along with other B/GFA creations such as the BIIGC and BIC – in a way conforms to intergovernmentalism's idea of ‘de novo bodies’ (Hodson, 2019, pp. 2–3).…”
Section: The 1993 Downing Street Declaration and 1998 Belfast/good Fr...mentioning
confidence: 97%
“…• A historical institutionalist perspective, which couches decisions as being embedded within the prevailing institutional design of the EU as a whole (Verdun 2015) • An intergovernmental framework which asserts that responses to crises were limited by member state negotiations and lowest-common denominator decision-making (Hodson 2019); and • A neo-functionalist emphasis on the role of supranational and transnational actors, as well as financial market interdependence, which encouraged euro area members to seek "optimal" common solutions (Niemann and Ioannou 2015). 3 Lesson 3.…”
Section: Policy Highlightsmentioning
confidence: 99%